2002
DOI: 10.1016/s0022-5347(05)65303-7
|View full text |Cite
|
Sign up to set email alerts
|

Erectile Dysfunction After Radical Prostatectomy: Hemodynamic Profiles and Their Correlation With the Recovery of Erectile Function

Abstract: These data imply that the longer the duration of erectile dysfunction after radical prostatectomy, the greater the risk of venous leakage. Furthermore, it appears that the prognosis for the return of functional erection is worst when venous leakage is present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
128
1
9

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 234 publications
(142 citation statements)
references
References 31 publications
4
128
1
9
Order By: Relevance
“…20 A penile hemodynamic study on NSRP patients who had no pharmacological support in the initial 12 months after surgery revealed a progressive incidence of venous leakage varying from 14% at 4 months to 50% at more than 12 months. 21 Similarly, in the study of Montorsi et al 1 53% of patients who did not self-inject with alprostadil in the first 4 months after surgery had a colour Doppler diagnosis of venous leakage vs only 17% of the treatment group. Schwarts et al 22 evaluated the cavernosal smooth muscle content in 40 patients before undergoing NSRP and after 6 months of postoperative treatment with sildenafil.…”
Section: Patients Bother For Sexual Function After Nsrpmentioning
confidence: 91%
“…20 A penile hemodynamic study on NSRP patients who had no pharmacological support in the initial 12 months after surgery revealed a progressive incidence of venous leakage varying from 14% at 4 months to 50% at more than 12 months. 21 Similarly, in the study of Montorsi et al 1 53% of patients who did not self-inject with alprostadil in the first 4 months after surgery had a colour Doppler diagnosis of venous leakage vs only 17% of the treatment group. Schwarts et al 22 evaluated the cavernosal smooth muscle content in 40 patients before undergoing NSRP and after 6 months of postoperative treatment with sildenafil.…”
Section: Patients Bother For Sexual Function After Nsrpmentioning
confidence: 91%
“…Patients tested later in the study had higher degrees of venous leakage than those tested earlier, although this did not hold true for arterial insufficiency. 23 Patients with venous leakage had significantly higher levels of ED than those solely with arterial insufficiency or normal hemodynamics, as it is likely the end result of fibrosis. As a result, these patients are not likely to have a satisfactory response to phosphodiesterase-5 inhibitors (PDE5I's).…”
Section: Pathophysiologymentioning
confidence: 92%
“…This may be associated with the time-dependent increase in the incidence of venous leak found in patients as they recover from RP. 23 The partial pressure of oxygen (pO 2 ) within the corpus cavernosum is significantly higher in the erect vs the flaccid state. 24 Furthermore, patients after RP lose the normal 3-5 nocturnal erections per night, a source of high arterial oxygen tension for 1 to 3.5 h per night.…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…This loss of smooth muscle beneath the tunica leads to venous leak and is evident clinically as venogenic ED. 11 Mulhall and coworkers 12 have shown that the longer the patient waits after surgery before initiating erectile function, the more likely it is that venous leak will develop, implying underlying corporal smooth muscle fibrosis. Finally, penile shortening is frequently reported by patients and partners following RP and believed to be a result of corporal fibrosis, increased apoptosis and de novo Peyronie disease formation.…”
Section: Pathophysiology Of Postprostatectomy Erectile Dysfunctionmentioning
confidence: 99%